Investigating the Predictive Validity of the COMPASS Pilot Selection Test. Issue 3 (3rd July 2021) - González Cabeza, Iñaki; Molesworth, Brett; Good, Malcolm; Caponecchia, Carlo; Steffensen, Rasmus
ABSTRACT: Objective : The present study examined the predictive validity of a widely used pilot selection test known as COMPASS, in terms of its ability to distinguish between candidates and predict individuals' aptitude for flying. Background: The Computerized Pilot Aptitude Screening System, more commonly known as COMPASS is a widely used selection test for ab-initio pilots. However, a literature search failed to uncover any research examining its predictive validity. Method: Thirty-five trainee pilots completed COMPASS, along with a simulated flight on a computer-based flight simulator to obtain an objective flight performance measure. Hours to flying milestones, including first solo and Recreational Pilot License, along with more subjective measures such as performance ratings by flying instructors were also compared to COMPASS. Twenty non-pilots also completed COMPASS. Results: The results revealed COMPASS to be effective in distinguishing between trainee pilots and non-pilots. However, there was no relationship between COMPASS scores and the various flight performance measures. Conclusion: These results should aid decision-makers when considering the viability of pilot selection tests, and reiterate the importance of using multiple methods/tools when attempting to select appropriate candidates for a specific role.